Partial oxidation of diesel fuel by plasma – Kinetic aspects of the reaction. (7th September 2017) - Dinh, Duy Khoe; Kang, Hee Seok; Jo, Sungkwon; Lee, Dae Hoon; Song, Young-Hoon
Abstract: Plasma reforming of fuel has recently been studied for possible applications in hydrogen generation and plasma assisted combustion. However, the kinetic aspects of plasma reforming have not been well understood yet, especially for the reforming of liquid fuels. In this study, a kinetic model was derived for the analysis of diesel partial oxidation assisted by plasma. Using a rotating arc as the plasma source, the effects of the oxygen-to-fuel ratio, specific energy input, temperature, and residence time on the reaction kinetics were investigated. A derived reaction model successfully describes the changes in the selectivity towards hydrogen relative to the amount of energy provided for the generation of plasma and the oxygen-to-fuel ratio in the reforming process. Highlights: Plasma reforming of diesel fuel was investigated. Parameters for the maximum hydrogen selectivity were investigated experimentally. The length of plasma reactor can be optimized based on the optimal time scale. A kinetic model is successfully proposed for prediction of hydrogen generation.